Konsep Maqâmât dalam Tradisi Sufistik K.H. Ahmad Asrori al-Ishaqy - Rosidi Rosidi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2014)
The article discusses the concept of sufistic thinking of K.H. Ahmad Asrori al-Ishaqy, the  murshid  (the spiritual guide) of al-Qâdirîyah wa al-Naqshabandîyah  tariqa  and the founder of al-Fithrah Islamic Boarding School in Kedinding Lor 99 Kenjeran Surabaya. In this article, the writer focuses mostly on the stages of the sufistic thinking of Kiai Asrori, because there are many sufistic concept that he stated. In addition, the writer tries to unveil Kiai Asrori?s concepts on sufistic realm which are implemented in daily lives, not only by himself, but also by his pupils and his followers. The purpose of this research is to describe the sufistic concept of Kiai Asrori, focusing on the stage (maqâmat) which has been stated in his public sermon, his statement stated for certain people, and also by his scipts. Besides, the purpose of this research is also to describe about how to implement his concepts in daily lives. The writer argues that the concept of the  maqâmat  stated by Kiai Asrori is different from other Islamic mysticism figure before him not only in terms of numbers but also in orders. The most significant difference is that the followers do not have to follow the stage step by step. According to him, his followers may choose the  maqâmatwhich are suitable with their ability.